PENGEMBANGAN BAHAN AJAR FLASHCARD BERBASIS CANVA UNTUK MENINGKATKAN KETERAMPILAN MEMBACA BAB 3 PENGOBAR SEMANGAT - Syailen Apriandini, Putri; Rostikawati, Teti; Wijaya, Ade (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research applies the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. A total of 37 class III students were designated as test subjects to develop and evaluate the effectiveness of the designed teaching materials. Validation of teaching materials was carried out by three experts, namely media experts, linguists, material experts, with media expert validation results of 90.66%, linguist validation results of 94.66%, material validation results of 94% with average results The 92.66% included in the